2014
DOI: 10.1371/journal.pone.0106601
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 Interacts with and Regulates Paraoxonase-2, an Enzyme Critical for Neuronal Survival in Response to Oxidative Stress

Abstract: Loss-of-function mutations in DJ-1 (PARK7) gene account for about 1% of all familial Parkinson's disease (PD). While its physiological function(s) are not completely clear, DJ-1 protects neurons against oxidative stress in both in vitro and in vivo models of PD. The molecular mechanism(s) through which DJ-1 alleviates oxidative stress-mediated damage remains elusive. In this study, we identified Paraoxonase-2 (PON2) as an interacting target of DJ-1. PON2 activity is elevated in response to oxidative stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 80 publications
3
31
0
Order By: Relevance
“…The ability of DJ-1 to protect from oxidative stress in several cell types has been widely reported [2528]. Mutations and deletion in the DJ-1 gene (PARK7) result in early-onset PD in patients and in loss of the entire protein or loss-of-function versions of the protein [6].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DJ-1 to protect from oxidative stress in several cell types has been widely reported [2528]. Mutations and deletion in the DJ-1 gene (PARK7) result in early-onset PD in patients and in loss of the entire protein or loss-of-function versions of the protein [6].…”
Section: Discussionmentioning
confidence: 99%
“…These windows of susceptibility are of interest for neurodegenerative diseases, as evidence mounts for mitochondrial dysfunction and elevated oxidative stress as key mediators of diseases such as Alzheimer and Parkinson’s [17, 18, 30]. Recent data suggest that PON2 interacts directly with DJ-1 (PARK7), allowing DJ-1 to exert antioxidant properties through the regulation of PON2 [31]. Loss of function mutations in DJ-1 are associated with some familial forms of Parkinson’s disease [32], offering a potential link between PON2 and neurodegenerative disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical-induced oxidative stress linked to PD pathogenesis has been widely reported, particularly 6-OHDA, MPTP, paraquat and rotenone (Cantu et al, 2011;Gao et al, 2014;Lu et al, 2015b;Parsanejad et al, 2014). These chemicals mainly impair mitochondrial function such as inhibiting complex I of the electron transport chain, resulting in the production of ROS.…”
Section: Methods Of Identifying Apoptosis or Cell Deathmentioning
confidence: 99%
“…Impaired DJ-1 activity could contribute to PD pathogenesis by lacking this transnitrosylation activity and subsequently lacking the ability to prevent neuronal cell death by oxidative stress. Another study reported that DJ-1 exerted neuroprotective effects via PON2, and PON2-deficient neurons were hypersensitised to MPP-induced oxidative stress (Parsanejad et al, 2014). Furthermore, DJ-1 was characterised as a metal-binding protein able to bind to copper and toxic mercury ions in vitro and protect metal-induced cell death by oxidative stress, and this protection was lost with the PD-mutated variants of DJ-1 (Bjorkblom et al, 2013).…”
Section: Summary Of Mechanism(s)mentioning
confidence: 99%
See 1 more Smart Citation